Pengaruh Metode Mengajar Dan Sikap Siswa Terhadap Pengetahuan Sosial - Nurdin, Nurdin (FKIP Universitas Lampung, 2017)
Abstract: The influence of teaching methods and students’ attitudes toward social knowledge. The article describes the results of this study the effect of teaching methods by using lecture and discussion on social knowledge based attitudes. The study was carried out experimentally with a 2x2 factorial design to the group of students at SMA Negeri 3 South Tambun, Bekasi. Datas were analyzed by analysis of variance of two lanes, and Tukey test. Based on the result of datas anaylizes,there was an interaction effect between teaching methods and students’ attitudes toward social knowledge. Keywords: teaching, lectures, discussions, student attitudes, social knowledgeDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701